The transcription factor Spores Absent A is a PKA dependent inducer of Dictyostelium sporulation - Yoko Yamada (Nature Portfolio, 2018)
Abstract Sporulation in Dictyostelium fruiting bodies evolved from amoebozoan encystation with both being induced by cAMP acting on PKA, but with downstream components still being unknown. Using tagged mutagenesis to find missing pathway components, we identified a sporeless mutant defective in a nuclear protein, SpaA. Expression of prespore genes was strongly reduced in spaA- cells, while expression of many spore stage genes was absent. Chromatin immunoprecipitation (ChIP) of a SpaA-YFP gene fusion showed that (pre)spore gene promoters bind directly to SpaA, identifying SpaA as a transcriptional regulator. SpaA dependent spore gene expression required PKA in vivo and was stimulated in vitro by the membrane-permeant PKA agonist 8Br-cAMP. The PKA agonist also promoted SpaA binding to (pre)spore promoters, placing SpaA downstream of PKA. Sequencing of SpaA-YFP ChIPed DNA fragments revealed that SpaA binds at least 117 (pre)spore promoters, including those of other transcription factors that activate some spore genes. These factors are not in turn required for spaA expression, identifying SpaA as the major trancriptional inducer of sporulation.